Effect of video-based trauma-informed care training for nursing staff on seclusion and restraint of psychiatric inpatients: A non-randomized controlled study - Michi Miyake; Megumi Hazumi; Kentaro Usuda; Takahiro Kawashima; Maiko Fukasawa; Hisateru Tachimori; Daisuke Nishi (International Journal of Nursing Studies Advances)
Background: Trauma-informed care, based on the belief that past traumatic experiences induce problematic behavior, is being promoted through various initiatives in the United States and other countries. The specific effect of training that focuses solely on trauma-informed care for reducing seclusion and restraint in psychiatric settings remains unknown. In this non-randomized controlled trial, we examined the effectiveness of a video-based trauma-informed care training program for nursing staff, with seclusion and restraint times as the outcome. Methods: Six of the 11 participating hospitals interested in trauma-informed care training were allocated to the intervention group, while the remaining five were assigned to the control group.The intervention ran from November 2021 to January 2022 in Japan. Data were collected using a specialized psychiatric monitoring system from April 2020 to October 2021 pre-intervention and from February 2022 to January 2023 post-intervention. The difference-in-differences analysis compared seclusion and restraint times between the groups. Results: During the data collection period, one hospital in the intervention group was excluded due to a change in ward function. Patients admitted to the remaining hospitals (5,050 in the intervention group and 4,830 in the control group) were included in the analysis. The analysis showed that the estimated difference-in-differences coefficient of average restraint time decreased significantly by -0.24 (p = 0.01) at 6 months post-intervention, although seclusion time was not significantly decreased. Conclusions: From the results of this non-randomized controlled trial, we found that video training focused solely on trauma-informed care may effectively reduce restraint time for inpatients. This accessible approach has the potential for broader adoption in clinical practice and may help reduce the use of coercive measures. Trial registration: The study was registered in the University Hospital Medical Information Network Clinical Trials Registry on 31 October 2021 (UMIN-CTR ID: UMIN000045879).